The Ambivalence of Scarcity and Other Essays - Dumouchel, Paul, 1951- (Book collections on Project MUSE., 2014)
First published in French in 1979, "The Ambivalence of Scarcity" was a groundbreaking work on mimetic theory. Now expanded upon with new and never-before-published conference texts and essays, this version explores Rene Girard's philosophy in three sections: economy and economics, mimetic theory, and violence and politics in modern societies. The first section argues that though mimetic theory is in many ways critical of modern economic theory, this criticism can contribute to the enrichment of economic thinking. The second section explores the issues of nonviolence and misrecognition (meconnaissance), which have been at the center of many discussions of Girard's work. The final section proposes mimetic analyses of the violence typical of modern societies, from high school bullying to genocide and terrorist attacks. Politics, Dumouchel argues, is a violent means of protecting us from our own violent tendencies, and it can at times become the source of the very savagery from which it seeks to protect us. The book's conclusion analyzes the relationship between ethics and economics, opening new avenues of research and inviting further exploration